2000
DOI: 10.1002/1097-4636(20000905)51:3<398::aid-jbm14>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Anodic oxidation and hydrothermal treatment of titanium results in a surface that causes increased attachment and altered cytoskeletal morphology of rat bone marrow stromal cells in vitro

Abstract: Previous studies have suggested the usefulness of a new coating method-namely, the forming of a thin hydroxyapatite (HA) layer on commercially pure titanium (cpTi) by anodization and hydrothermal treatment-for use as a dental root implant material. In vivo and in vitro studies confirmed that an HA layer on cpTi (HA/cpTi) implants showed good compatibility with bone tissue, rat bone marrow stromal (RBM) cells, and immune cells. The aim of the present investigation was to further characterize the in vitro early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
79
3
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(94 citation statements)
references
References 27 publications
8
79
3
1
Order By: Relevance
“…Okumura et al (2001) suggest that the lack of vinculin-containing adhesion sites in the osteoblasts on HA is because they are of a more differentiated phenotype. The differential phenotype theory is also cited in other studies (Schwartz and Boyan, 1994;Takebe et al, 2000). The results from this study, however, indicated that this might not have been the case.…”
Section: C Baxter Et Al Fibroblast and Osteoblast Adhesionmentioning
confidence: 44%
See 1 more Smart Citation
“…Okumura et al (2001) suggest that the lack of vinculin-containing adhesion sites in the osteoblasts on HA is because they are of a more differentiated phenotype. The differential phenotype theory is also cited in other studies (Schwartz and Boyan, 1994;Takebe et al, 2000). The results from this study, however, indicated that this might not have been the case.…”
Section: C Baxter Et Al Fibroblast and Osteoblast Adhesionmentioning
confidence: 44%
“…HA is thought to be biocompatible surface coating that can accelerate properties of bone healing (Chou et al, 1999). Takebe et al (2000) show that cells on HA have a flattened spreading morphology with numerous filopodia and that they are intimately associated with the surface, but that cell adhesion is greater on commercially pure titanium at 60 and 120 minutes after introduction. Okumura et al (2001) also demonstrate that fewer vinculin containing adhesion plaques are present in osteoblasts on HA at 12 and 24 hours, when compared to titanium.…”
Section: C Baxter Et Al Fibroblast and Osteoblast Adhesionmentioning
confidence: 99%
“…MAO can make titanium implant surface bioactive, porous, and nanocrystallized. Takebe et al [152] reported that the thin HA layer formed by anodization and hydrothermal treatment on the surface of cpTi implant materials showed desirable cellular behavior. The thin HA layer on the 76 X cpTi surface affects cellular attachment and spreading, and a thin HA layer appears to be more osteoconductive to cellular attachment than untreated cpTi as illustrated in Fig.…”
Section: Anodic Oxidationmentioning
confidence: 99%
“…A group of researchers reported that desirable cellular behaviour such as cell growth, cell attachment, etc. can be obtained from the thin HA layer on the surface of CP-Ti which was produced by anodization and subsequently followed by hydrothermal treatment (Takebe et al, 2000). It is observed that cellular attachment and spreading are affected by this thin HA layer on the CP-Ti surface.…”
Section: Anodic Oxidationmentioning
confidence: 99%